2007
DOI: 10.1007/s11748-007-0134-6
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular thrombus with a normal heart

Abstract: A 44-year-old man was found to have a left ventricular mass by transthoracic echocardiography. He had had multiple events of systemic embolization over the last few years. The heart was not dilated, and heart function was normal. Surgical excision was recommended to avoid further embolization. A transverse aortotomy was carried out under cardioplegic cardiac arrest with standard cardiopulmonary bypass. A transaortic video-assisted endoscopic procedure was performed. The mass was resected endoscopically without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…This was followed by semi-rigid endoscopes in four [7, 9, 21, 29], flexible endoscopes in three [2, 3, 30] and mixture of rigid and flexible endoscopes in one study [11]. In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was followed by semi-rigid endoscopes in four [7, 9, 21, 29], flexible endoscopes in three [2, 3, 30] and mixture of rigid and flexible endoscopes in one study [11]. In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35]. Other adjunct endoscopic instruments such as forceps, graspers, scissors, suckers or retractors were used in 13 studies [2, 3, 12, 13, 15, 19, 21, 25, 30, 32, 34, 35, 37]. In the remaining it was not clear whether open surgical or endoscopic instruments were used.…”
Section: Resultsmentioning
confidence: 99%
“…Protein C and S deficiency, antiphospolipid syndrome, myeloproliferative disorders, idiopathic hypereosinophilic syndrome, pheochromocytoma, and Takatsubo cardiomyopathy were reported to be related with thrombus formation in patients with a normal LV ejection fraction (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of detectable cardiac disease, left ventricular thrombosis is rare and described only anecdotally. Many of these patients have prothrombotic disorders such as protein C deficiency [12], protein S deficiency [13], essential thrombocythemia [14] and antiphospholipid antibody syndrome [15]; however, there are no reports of patients with left ventricular thrombus associated with IDA. Because our patient had no other detectable prothrombotic disorders, we concluded that IDA was the sole cause of left ventricular thrombosis.…”
Section: Discussionmentioning
confidence: 99%